Telecommunications essentials : the complete global source - Goleniewski, Lillian (Addison Wesley Professional, 2006)
"In this updated and expanded edition of her excellent telecommunications primer, Lili explains in just the right detail everything you need to know to become fluent in this most important and fascinating industry. Besides including a satisfying amount of expert technical detail, the book also discusses equally crucial aspects of how communications technology affects society, culture, and politics. Electronic communications is changing the world for the better; learn from Lili's expertise how you, too, can participate in the revolution."--Steve Riley, senior security strategist, Microsoft Corporation "The book you hold in your hand is a rarity. In more than thirty years of teaching, administration, and research in telecommunications, I have never found a single book that could serve these diverse areas. The search is over. Telecommunications Essentials is best-of-breed in telecommunications publishing and represents the most thorough, comprehensive, and forward-looking resource to date. Both student and practitioner alike will find the unique blend of introductory and advanced material a 'one-stop-shop.' If it was a movie, this book would receive two thumbs up!" -Dr. Art St. George, manager of advanced technologies, University of New Mexico " Telecommunications Essentials should be on the shelf of every professional working in voice and data networking. It is the first place I go when I need to look up something that I am unsure of or when I encounter a new or unfamiliar term. I have been using Telecommunications Essentials now for two years as the course text for business technology students taking Introduction to Telecommunications. My course covers the entire book and the students end up with a practical knowledge base of the components, technologies, and connectivity that make today's networks work. This new edition is most welcome since it includes new advances in the areas of fiber optics, wireless, Voice over IP, and broadband technologies that have emerged since the publication of the first edition. This new edition will replace my well-worn copy of my first edition of Telecommunications Essentials, which has served me well so far." -Robert Hudyma, professor of business, Ryerson University "This is an excellent reference book on telecommunications. It's up-to-date on the latest technology, it's comprehensive, and most of all, it's easy to read and understand. Lili has the rare ability to explain very complex subjects well. If you ...